Association between atopic dermatitis and hypertension: a systematic review and meta‐analysis. (30th September 2021) - Yousaf, M.; Ayasse, M.; Ahmed, A.; Gwillim, E.C.; Janmohamed, S.R.; Yousaf, A.; Patel, K.R.; Thyssen, J.P.; Silverberg, J.I.
Summary: Background: Previous studies have found conflicting results about the association of atopic dermatitis (AD) with hypertension. Objectives: To determine whether AD and AD severity are associated with hypertension. Methods: A systematic review was performed of published studies in Ovid MEDLINE, Embase, Scopus, Web of Science, and GREAT (Global Resource for EczemA Trials) databases. At least two reviewers conducted title/abstract, full‐text review and data extraction. Quality of evidence was assessed using the Newcastle–Ottawa Scale. Results: Fifty‐one studies met the inclusion criteria and 19 had sufficient data for meta‐analysis. AD was associated with higher odds of hypertension compared with healthy controls [increased in nine of 16 studies; pooled prevalence 16·4% vs. 13·8%; random‐effects regression, pooled unadjusted odds ratio (OR) 1·16, 95% confidence interval (CI) 1·04–1·30], but lower odds of hypertension compared with psoriasis [decreased in five of eight studies; 15·4% vs. 24·8% (OR 0·53, 95% CI 0·37–0·76)]. In particular, moderate‐to‐severe AD was associated with hypertension compared with healthy controls [increased in four of six studies; 24·9% vs. 14·7% (OR 2·33, 95% CI 1·10–4·94)]. Hypertension was commonly reported as an adverse event secondary to AD treatments, particularly systemic ciclosporin A. Limitations include lack of longitudinal studies or individual‐level data, and potential confounding. Conclusions: AD, particularly moderate‐to‐severe disease, was associated with increased hypertension compared with healthy controls, but with lower odds than for psoriasis. Abstract : What is already known about this topic? Previous studies have showed conflicting results regarding the association between atopic dermatitis (AD) and hypertension. What does this study add? This systematic review and meta‐analysis found that AD, particularly moderate‐to‐severe disease, is associated with increased odds of hypertension compared with healthy controls, especially among the US population. Linked Comment:  H. Ben Abdallah and C. Vestergaard. Br J Dermatol 2022; 186:203–204 . Plain language summary available online